Analysis and Minimization of Output Current Ripple of Multiphase Carrier-Based PWM Inverters - Dahono, Pekik Argo (Journal of Engineering and Technological Sciences, 2010)
Analysis  and  minimization  of  output  current  ripple  of  multiphase carrier-based PWM  inverters are presented in this paper.  Analytical expression of rms value of output current ripple of multiphase PWM inverters as a function of the reference signal is first derived. Based on this expression, it is shown that a pure sinusoidal signal is the optimum reference signal that results in minimum output  current  ripple.  Different  to  three-phase  PWM  inverters,  injection  of harmonics  into  the  sinusoidal  reference  signal  is  neither  necessary  nor  useful. The  rms  values  of  output  current  ripple  of  5-,  7-,  and  9-phase  PWM  inverters under various reference signals are compared. Experimental results are included to show the validity of the analysis method.